The Cyclopropylmethyl Free Radical Clock. Calibration for the Range 30-90°C - Mathew, Lukose K. (My University, 2016)
The Arrhenius equation for the ring opening isomerization of cyclopropylmethyl radicals (R•) to 3-buten-1-yl radicals (R•') for the 303-362 K temperature range was determined by thermolysis of cyclopropylmethyl [1-hydroxy-1-methylethyl] diazene in the presence of excess 1,1,3,3-tetra-methylisoindolin-2-yloxyl (Y•).
Rate constants for coupling of R• with Y• were assumed to be proportional to diffusion controlled rate constants (kd) and rate constants (ki) for the isomerization were calculated from kd (corrected) and product ratios (RY/R'Y). The temperature dependence of ki, given by log(ki/s^-1) = (13.9 ± 0.4) - (7.6 ± 0.1)/θ, is significantly different from that determined by Ingold and co-workers by kinetic epr spectroscopy in the temperature range 128-153 K; log(ki/s^-1) = (11.34 ± 0.85) - (5.94 ± 0.57)/θ, where θ = 2.3 RT kcal mol^-1.
Keywords: cyclopropylmethyl, free, radical, clock, calibration, isomerization